(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Introduction: Pregnant women have long been recognized as a vulnerable population during infectious disease pandemics due to physiological changes in the immune, pulmonary, cardiac and coagulation systems. It is essential to acquire knowledge of pregnancy outcomes, potential complications and neonatal health conditions born to an infected mother with COVID-19. Material and methods: This cross-sectional observational study was conducted in Combined Military Hospital (CMH), Jashore from June 2020 to July 2021 among 100 hospitalized laboratory-confirmed COVID-19 positive pregnant women, patients who had clinical symptoms of COVID but RT PCR negative were excluded. The aim of the study was to evaluate the clinical profile and maternal and fetal outcome of pregnancy. Relevant data were recorded in a preformed data collection sheet and analyzed by SPSS version 20. Results: Among 100 COVID-19 positive hospitalized pregnant women, the mean age of participants was 27years (range 19-40 years), Maximum infection rate observed during 12 to 28 weeks of gestation among the participants, 21% got infected at 37 to 40 weeks of gestation and 20% got infected at 32 to 36 weeks. Seventy-four percent patients underwent delivery during the study & 23% of them continued with ongoing pregnancy; 67 of the participants underwent LUCS and 7 vaginal deliveries were done, 3% had abortion and IUFD 1% ,61% were multipara and 39% were Primipara, associated co-morbidities were subclinical hypothyroidism(15%), pregnancy induced HTN(12%) and GDM(8%); 36% participants were asymptomatic and 44% had mild symptoms, rate of LUCS was higher than (90.64%) vaginal delivery. Among the 73 live births, 80.82% were term and 10.18% were preterm of neonates, small for gestational was seen in the case of 20.55% neonates. Testing for SARS-CoV-2 was performed in all neonatal throat swabs and found positive in one case only. Eighty-six percent neonates were well-baby and 9.58% neonates required NICU admission. There were 2 neonatal deaths due to severe prematurity and 2 babies were found to have congenital cardiac anomaly and cleft lip, cleft palate. Though 36% of patients were asymptomatic but 10% were severe and in the critical stage. HDU support needed for 8% of patients and ICU support for 6%. Conclusion: This cross-sectional study supports that pregnant women with COVID-19 infection are at increased risk of adverse pregnancy and birth outcomes and a low risk of congenital transmission. Availability of ICU in critical conditions is needed for better pregnancy outcomes. J Bangladesh Coll Phys Surg 2022; 40: 10-16